Identification of 99% of CFTR gene mutations in Bulgarian-, Bulgarian Turk-, and Roma cystic fibrosis patients - Petrova, Guergana; Yaneva, Nadezhda; Hrbková, Jana; Libik, Malgorzata; Savov, Alexey; Macek, Milan (Molecular genetics & genomic medicine, 2019)
BACKGROUND: The spectrum and frequencies of CFTR mutations causing Cystic fibrosis (CF) varies among different populations in Europe, and beyond. METHODS: We identified 98.9% of all CFTR mutations in a representative cohort of 140 CF patients comprising 107 Bulgarian- (BG), 17 BG Turk-, and 16 BG Roma cases. The compiled clinical and genotype dataset includes 110 previously analyzed patients with 30 cases currently analyzed for rare CFTR variants by massively parallel sequencing of the entire CFTR coding region and adjacent introns combined with the analysis of intra-CFTR rearrangements. RESULTS: Altogether 53 different mutations, of which 15 newly identified in the BG CF population, were observed. Comparison of clinical and laboratory data between individual BG ethnic groups proved that BG Roma have a more severe nutritional status and are younger than other CF patients, as well as that the spectrum mutations differs between them. CONCLUSION: This collaborative study improves genetic counselling in BG, facilitates introduction of multitier CF neonatal screening and fosters public health measures for improvement of care in the Roma CF population.
Keywords: Genetic Predisposition to Disease; molekulární epidemiologie; Cystic Fibrosis Transmembrane Conductance Regulator; Bulgarians; genotyp; Introns; Male; Bulharsko; kojenec; Genotype; mladiství; Cohort Studies; Middle Aged; mužské pohlaví; mutace; Infant; Adult; mladý dospělý; Romové; kohortové studie; dítě; Cystic Fibrosis; Child; Child, Preschool; CFTR gene; Young Adult; ženské pohlaví; Mutation; protein CFTR; Humans; předškolní dítě; Bulgaria; High-Throughput Nucleotide Sequencing; Molecular Epidemiology; Bulgarian Turks; lidé středního věku; vysoce účinné nukleotidové sekvenování; Roma; introny; cystic fibrosis; dospělí; genetická predispozice k nemoci; Female; Adolescent; lidé; cystická fibróza